2022
DOI: 10.3390/ijms23031327
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Type 1 and Type Z Protein Phosphatases Reveals D615 as a Key Residue for Ppz1 Regulation

Abstract: Type 1 Ser/Thr protein phosphatases are represented in all fungi by two enzymes, the ubiquitous PP1, with a conserved catalytic polypeptide (PP1c) and numerous regulatory subunits, and PPZ, with a C-terminal catalytic domain related to PP1c and a variable N-terminal extension. Current evidence indicates that, although PP1 and PPZ enzymes might share some cellular targets and regulatory subunits, their functions are quite separated, and they have individual regulation. We explored the structures of PP1c and PPZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…We show here that, indeed, this region is vital for regulation of Ppz1. This is in keeping with the very recent evidence obtained by chemical crosslinking showing that the vast majority of interactions detected between the catalytic C-terminal domain of Ppz1 and Hal3 involve residues located within this Nterminal extension [33].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We show here that, indeed, this region is vital for regulation of Ppz1. This is in keeping with the very recent evidence obtained by chemical crosslinking showing that the vast majority of interactions detected between the catalytic C-terminal domain of Ppz1 and Hal3 involve residues located within this Nterminal extension [33].…”
Section: Discussionsupporting
confidence: 90%
“…1A ). These specific regions were selected based on two criteria: (a) sequence conservation among different yeast species, and (b) the results of our recently reported chemical cross‐linking experiments [ 33 ], which suggested several interactions between the catalytic C‐terminal domain of Ppz1 and diverse regions within the N‐terminal Hal3 extension. These versions were cloned in plasmid pWS93, to allow multicopy expression from the ADH1 promoter, and were subsequently introduced into diverse yeast strains to test for the function of these Hal3 versions as Ppz phosphatase regulators.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned above, the role of Hal3 in salt tolerance and cell cycle regulation [71,72] was explained by its identification as a protein able to bind to Ppz1 at its C-terminal catalytic domain and inhibit its phosphatase activity [21,46]. However, in spite of considerable effort, the molecular basis for this inhibitory mechanism is not fully understood [73][74][75][76][77][78].…”
Section: Hal3: Just An Inhibitor Of Ppz1 Activity?mentioning
confidence: 99%
“…Hal3 can be recovered bound to Ppz1 when both proteins are simultaneously expressed in E. coli [ 39 ]. This fact was exploited to carry out chemical cross-linking experiments, involving full Hal3 and the C-terminal catalytic domain of Ppz1, followed by the identification of the covalently bound peptides by mass spectrometry [ 41 ]. It was found that most Hal3 links were restricted to the N-terminal half and the first third of the conserved PD domain.…”
Section: Structural Insights Into the Moonlighting Functions Of Hal3mentioning
confidence: 99%